Key technologies and challenges in online adaptive radiotherapy for lung cancer - Baiqiang Dong; Shuohan Zheng; Kelly Chen; Xuan Zhu; Sijuan Huang; Xiaobo Jiang; Wenchao Diao; Hua Li; Lecheng Jia; Feng Chi; Xiaoyan Huang; Qiwen Li; et al. (Chinese Medical Journal)
Abstract. Definitive treatment of lung cancer with radiotherapy is challenging, as respiratory motion and anatomical changes can increase the risk of severe off-target effects during radiotherapy. Online adaptive radiotherapy (ART) is an evolving approach that enables timely modification of a treatment plan during the interfraction of radiotherapy, in response to physiologic or anatomic variations, aiming to improve the dose distribution for precise targeting and delivery in lung cancer patients. The effectiveness of online ART depends on the seamless integration of multiple components: sufficient quality of linear accelerator-integrated imaging guidance, deformable image registration, automatic recontouring, and efficient quality assurance and workflow. This review summarizes the present status of online ART for lung cancer, including key technologies, as well as the challenges and areas of active research in this field.